Leveraging AI for Competency Valuation of People with Disabilities in Oman - Halawi, Ali H.; Rasheed, Razeena; Wahaibi, Mahmood Ali Al; Hinai, Fatima Al; Uthaman, Neena (Journal of Cultural Analysis and Social Change, 2025)
This study examines the critical role of skill assessment and competency mapping for the inclusion and empowerment of people with disabilities (PwDs) in Oman. The introduction highlights the increasing importance of competency mapping in today's competitive environment and its connection to strengthening the workforce for a competitive advantage. The primary objective of this research is to review existing literature on skill assessment and competency mapping for physically disabled individuals in Oman, examine current frameworks and available programs, and identify gaps in the literature to propose strategies for addressing them. The methodology involves a literature review, analyzing existing quantitative and qualitative research, and utilizing theoretical frameworks such as Competency-Based Education (CBE), the Social Model of Disability, and Human Capital Theory to inform the analysis. The results indicate a significant gap in research concerning competency mapping and skill assessment specifically among individuals with physical disabilities in Oman, with existing studies largely focusing on psychological, behavioral, and social challenges, as well as employment and training opportunities. The discussion emphasizes that addressing these challenges through inclusive practices and supportive frameworks will enhance opportunities for PwDs, contributing to a more equitable society. The originality and value of this study lie in its identification of a research void in culturally appropriate skill assessment tools and longitudinal studies on the impact of competency mapping on employment outcomes for PwDs in Oman, while also advocating for the responsible integration of AI and collaboration between stakeholders to promote inclusive assessment and employment.